Vocational Guidance: Harmonization of Points of View - N. S. Pryazhnikov; L. S. Rumyantseva; N. L. Sokolova; L. B. Bakhtigulova (Научный диалог, 2018)
The problem of harmonization of different views on career-oriented work, due to the diversity of ideas about life and career success, as well as about the ways to success, is considered. The authors conditionally called the phenomenon of the plurality of interpretations of the content of this concept “vocational orientation pluralism”. The positions of the self-determining personality, psychologists-career advisors, methodologists, scientist- career guides, employers are considered. Differences in the understanding of the essence of vocational guidance by all named subjects of interaction are characterized. The mismatch of their expectations in relation to the professional advisers is emphasized. It is alleged that managers of enterprises and organizations conduct different personnel policies, depending on their awareness of the importance of human potential. Vocational guidance is interpreted in the context of the cultural and historical development of society. The authors identify the points of incompatibility of different positions in the understanding of vocational guidance and offer generalized variants (ways) for harmonizing opinions. The first group consists of variants of “external” harmonization, that is, ways of coordinating opinions between subjects that in one way or other participate in vocational guidance. The second group consists of variants of “internal” harmonization that is between people representing one social or professional group, interested in solving career counseling issues.